Object-Oriented Analysis and Design: Understanding System Development with UML 2.0 - O docherty (Mike) (2005)
Object-Oriented Analysis and Design ; OOAD ; UML
22.5
Keywords: Object-Oriented Analysis and Design ; OOAD ; UML